Astronomical Study of Abdurrahman Özlem’s Prayer Time Concept in Abnormal Regions - Hayati, Atika; Jannah, Elly Uzlifatul; Sulthon, Muhammad (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
The determination of prayer times in high-latitude regions has long faced significant challenges due to the imbalance between day and night durations. The lack of clear guidance in the Qur’an and Hadith regarding this phenomenon has led various scholars and experts to propose their ijtihad. One such figure is Abdurrahman Özlem, a Turkish astronomer. This study aims to explore Özlem’s concept of determining prayer times in abnormal regions and analyze it from an astronomical perspective. Using a qualitative descriptive-analytical approach, this research integrates modern astronomical principles within the framework of contemporary Islamic jurisprudence. Data were collected through online interviews and document studies. Özlem proposes a method based on proportional division of day and night durations, using 12:00 noon and 24:00 midnight as reference points. He utilizes solar hour angles adjusted to local time zones (regional time), resulting in prayer time estimations that are both astronomically precise and practically relevant. This study makes a significant contribution to scientific knowledge by demonstrating the integration of modern astronomy into Islamic legal reasoning to address the challenges of worship in extreme regions. While promising as an alternative guide for Muslims in such areas, further studies are needed to assess its applicability across different madhhabs and geographic contexts.